Christianity in Persia and the Status of Non-Muslims in Modern Iran - Gorder, Christian A. (Lexington Books, 2010)
Writing on an often overlooked section of contemporary Persian culture, A. Christian Van Gorder provides a comprehensive and readable introduction to the experience of Christians and other non-Muslims in Iran throughout history and into the present day. Van Gorder gives a fascinating account of the history of Christianity in Persia. By debunking the common misconceptions and stereotypes driven by recent political events and the media, he shows the current relationship that Muslim majority in Iran has taken toward people of other faiths.